METODE INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS (IPA): PERSEPSI TENAGA KESEHATAN DAN PASIEN TERHADAP PENGOBATAN ASMA - Marthy Meliana Ariyanti Jalmav; Amelia Lorensia; Ananta Yudiarso; Daniel Maranatha (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Pharmaceutical care by pharmacists in the management have an important role of treatment monitoring. Optimal asthma treatment for patients requires cooperation between patients, healthcares, involving doctors, nurses, and pharmacists. Therefore the purpose of this study is to know the perception of healthcares and patients about asthma treatment and pharmaceutical cares on asthma mangement. The method of this study is based on phenomenological perspective with interpretative phenomenological analysis (IPA) on pulmonologist, outpatient asthma, pharmacist and nurse who directly correlated with asthma treatment at a hospital in Surabaya conducted for two years using purposive sampling. The results of this study indicate that asthma patients know how to manage asthma and use asthma drugs well. In addition it is known that asthma patients feel the role of doctors in the treatment of asthma is very dominating; pulmonologists and nurses perceive that the role of pharmacists is limited to drug delivery; and pharmacists assume that their role has been well done although not all patients get the same asthma treatment education. It is therefore necessary to evaluate the role of pharmacist in performing its role in the treatment of this asthma in order for a more harmonious collaboration.